1988
DOI: 10.1136/thx.43.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative neuralgia in the leg after saphenous vein coronary artery bypass graft: a prospective study.

Abstract: The degree of cutaneous sensory deficit in the leg was assessed after removal of the long saphenous vein in 50 consecutive patients undergoing coronary artery bypass vein grafts randomly assigned subcutanous sutures or a single layer of sutures. Removal of the vein and repair of the leg incision were done by the same team of surgeons. In group 1 (25 patients) the leg incision was repaired with "00" Dexon subcutaneous and "00" prolene subcuticular sutures while in group 2 (25 patients) closure was effected by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 1 publication
0
22
0
4
Order By: Relevance
“…Nair et al (1988) performed a prospective study looking at suture techniques and its affect on postoperative neuralgia. They assigned patients to either subcutaneous and subcuticular sutures or simple interrupted sutures for closure of the leg wound.…”
Section: Discussionmentioning
confidence: 99%
“…Nair et al (1988) performed a prospective study looking at suture techniques and its affect on postoperative neuralgia. They assigned patients to either subcutaneous and subcuticular sutures or simple interrupted sutures for closure of the leg wound.…”
Section: Discussionmentioning
confidence: 99%
“…(4,6,14) Dobfie je znám i vztah mezi v˘skytem neurologick˘ch komplikací a technikou uzávûru incize. (4,15) EVH umoÏÀuje provést odbûr prakticky z jedná incize potfiebné k zavedení endoskopu. Po fázi uvolnûní kmene VSM tupou disekcí jsou postranní vûtve uzavírány hemoklipy, bipolární koagulací ãi pomocí harmonického skalpelu.…”
Section: Diskuseunclassified
“…This may be due to the design of our study. Nair et al (1988) used a similar technique for wound closure after saphenectomy and reported the prevalence of pain and tingling as 62%. We found the prevalence of these complications as 56%.…”
Section: Discussionmentioning
confidence: 99%